Biofilm Inhibitory Effect of Chemogenic Nano Zerovalent Iron Against Biofilm of Clinical Isolate of Staphylococcus aureus - Ganesh, S.; Karthick Raja Namasivayam, S. (Asian Journal of Chemistry, 2012)
Due to their sub colloidal size and unique molecular and/or atomic structures, many nanomaterials have been shown to possess distinctive mechanical, magnetic, optical, electronic, catalytic and chemical properties that contribute to promising applications in machinery, energy, optics, electronics, drug delivery and medical diagnostics and they have a wide range of potential applications in biomedical fields and in water treatment as disinfectants or antibiofilm agents. In the present study, nano-zerovalent iron was synthesized by aqueous-phase reduction of ferrous sulfate using sodium borohydride as the reducing agent and the synthesized particles characterized by transmission electron microscopy which reveals spherical shape of particles with the size range of 25-30 nm. Biofilm inhibitory effect of synthesized nano zerovalent iron particles against clinical isolate of Staphylococcus aureus reveals distinct inhibition of biofilm with 95 % of inhibition and the biofilm matrix derived from nano zerovalent treated biofilm of S. aureus weakened due to reduction of biochemical composition of biofilm.